1997
DOI: 10.1007/s002239900285
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Expressed in Multinucleated Cells: Paget's Disease and Giant Cell Tumors versus Normal Bone

Abstract: Human osteoclasts are well characterized multinucleated cells whose function is the directed resorption of normal bone (NB). Osteoclastic bone destruction accompanies lytic solid tumors and myeloma as well as Paget's disease (PD) of bone and giant cell tumors of bone (GCTB). The mechanism of this stimulation of osteoclastic bone resorption is unknown. This study was designed to detect cytokines present in the multinucleated cells of PD and GCTB in order to determine whether cytokine abnormalities exist to acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Disruption of b-FGF (FGF-2) gene resulted in decreased bone mass and bone formation in mice (49). Pathological conditions such as Paget's disease of bone demonstrated increased levels of b-FGF expression in osteoclasts compared with normal bone (50). Therefore, local concentrations of osteotropic factors including b-FGF may have significant effects on HSP and HSF activation in both physiological and pathological conditions in modulating RANKL gene expression in stromal/osteoblastic cells present in the bone microenvironment.…”
Section: B-fgf Enhances Rankl Expression and Hsp-27 Phosphorylation Imentioning
confidence: 99%
“…Disruption of b-FGF (FGF-2) gene resulted in decreased bone mass and bone formation in mice (49). Pathological conditions such as Paget's disease of bone demonstrated increased levels of b-FGF expression in osteoclasts compared with normal bone (50). Therefore, local concentrations of osteotropic factors including b-FGF may have significant effects on HSP and HSF activation in both physiological and pathological conditions in modulating RANKL gene expression in stromal/osteoblastic cells present in the bone microenvironment.…”
Section: B-fgf Enhances Rankl Expression and Hsp-27 Phosphorylation Imentioning
confidence: 99%
“…Osteoclasts can be activated to secrete factors that act through autocrine and paracrine mechanisms to contribute to inflammation and autoimmunity (4). For example, osteoclasts from patients with Paget's disease or giant cell tumors of bone produce higher levels of various cytokines and growth factors, including IL-6 and platelet-derived growth factor, than cells from normal bone (5). In co-cultures, myeloma cells and osteoclasts constitutively secrete the proangiogenic factors, VEGF-A (vascular endothelial growth factor-A) and osteopontin (6).…”
mentioning
confidence: 99%
“…The quantitative estimate of numbers of cells staining was a = <20%, b = 20–60%, and c = >60%. The mean relative positivity was <1b = 0; 2a and 2b = 1; and 3b and 3c = 2 [24,25]. In this study, in some instances, no clear staining was observed for OPG at 4 and 6 months in animals on the 25% NR Mg diet, therefore, a minimum value of 0.01 was given to allow for calculation of RANKL/OPG ratio.…”
Section: Methodsmentioning
confidence: 76%
“…No difference in background localization was observed between Mg deficient and control rats. Cells and tissues stained specifically as described for the antigen in the literature [24,25]. Intensity was graded as 0 = no localization, 1 = weak localization, 2 = moderate, and 3 = strong localization.…”
Section: Methodsmentioning
confidence: 99%